How is cardiac troponin released from injured myocardium? - Mair, Johannes; Giannitsis, Evangelos (European heart journal - acute cardiovascular care, 2018)
Cardiac troponin I and cardiac troponin T are nowadays the criterion biomarkers for the laboratory diagnosis of acute myocardial infarction due to their very high sensitivities and specificities for myocardial injury. However, still many aspects of their degradation, tissue release and elimination from the human circulation are incompletely understood. Myocardial injury may be caused by a variety of different mechanisms, for example, myocardial ischaemia, inflammatory and immunological processes, trauma, drugs and toxins, and myocardial necrosis is preceded by a substantial reversible prelethal phase. Recent experimental data in a pig model of myocardial ischaemia demonstrated cardiac troponin release into the circulation from apoptotic cardiomyocytes as an alternative explanation for clinical situations with increased cardiac troponin without any other evidence for myocardial necrosis. However, the comparably lower sensitivities of all currently available imaging modalities, including cardiac magnetic resonance imaging for the detection of particularly non-focal myocardial necrosis in patients, has to be considered for cardiac troponin test result interpretation in clinical settings without any other evidence for myocardial necrosis apart from increased cardiac troponin concentrations as well.
First published December 27, 2017
Gesehen am 22.08.2018